New and little-known pygmy grasshoppers (Orthoptera: Tetrigidae) from Thailand - Storozhenko, Sergey Yu.; Dawwrueng, Pattarawich (Zootaxa, 2015)
An annotated list of 39 species in 25 genera and seven subfamilies of the pygmy grasshoppers (Orthoptera: Tetrididae) from Thailand is given; from these 18 species are recorded from this country for the first time. Five new species are described: Cotysoides gaponi sp. nov. (subfamily Metrodorinae), Eucriotettix anisyutkini sp. nov., Gavialidium bufocrocodil sp. nov., Scelimena bellula sp. nov. (subfamily Scelimeninae) and Phaesticus uvarovi sp. nov. (subfamily Discotettiginae). One species is transferred from Scelimena to Amphibotettix and a new combination is proposed: Scelimena hafizhaii Mahmmod, Idris et Salman, 2007 = Amphibotettix hafizhaii (Mahmmod, Idris et Salman, 2007), comb. nov. The previously unknown male of Falconius tschernovi Storozhenko, 2014 is described.